Konservasi vs Pariwisata Massal: Konflik Kebijakan dan TantanganBorobudur sebagai Warisan Budaya Dunia UNESCO - Darmawan, Fahrurozy (UI Scholars Hub, 2023)
The designation of Borobudur as a World Cultural Heritage by UNESCO in 1991 has introduced Borobudur Temple and its surroundings to the world and sparked the growth of mass tourism for decades. This article tries to discuss about tWorld Cultural Heritage area, mass tourism and conservation do not always go hand in hand. This study explores the tourism and conservation policies taken by the central and local government of Indonesia in managing the Borobudur area and looks at how these policies affect the development of the Borobudur area. The research method used is library research and policy analysis. It was found that policies that were oriented too biased in favor of its use tend to reduce the conservation function, visitor management management that continues to preserve the site. Theoretically, this research contributes to the model of policy management and development in heritage conservation areas. And practically, this research can be used as a policy reference for the government in managing and reducing conflict and friction between sectors.